KOINTEGRASI DAN KAUSALITAS INDEKS HARGA SAHAM GABUNGAN DAN DOW JONES INDUSTRIAL INDEX - Paulus Sulluk Kananlua (UNIVED Press, 2016)
This research is obviously intended to analyze the impact of global financial crisis which happened in America and surrogated by the Dow Jones Industrial Index (DJI) towards the Indonesian Stock Exchange, represented by the composite index (IHSG). The study is conducted by using time series data ranging from January 2007 to July 2014. Data used consists of 60 months observation. In order to examine the time series data, Vector Autoregressive Model (VAR) is employed. We run the statistical tool to estimate the respon caused by the shock of research variable. Before estimating the model of Vector Autoregression (VAR), the data used must following the unit root test, cointegration test, granger causality test, and then runned by using VAR model. Our result reveals that the data is not stationer at level, but stationer at first difference. The interpreted estimation output resulting from impulse response function and variance decomposition show that DJI’s respons is much bigger caused by the shock from DJI itself with average number stand on 99.36%. Further, the proportion of IHSG on average is 0.64%. Meanwhile the respon of IHSG sparked by the DJI is 53.10% on average. The remained value as 46.90% is caused by the shock from IHSG. Key Words: DJI, IHSG, VAR, Unit Root Test, Cointegration Test, Granger Test, Impulse Response,Variance Decomposition